2015
DOI: 10.1371/journal.pone.0139898
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Contextual and Task Performance and Interrater Agreement: Are There Any?

Abstract: Work performance is one of the most important dependent variables in Work and Organizational Psychology. The main objective of this paper was to explore the relationships between citizenship performance and task performance measures obtained from different appraisers and their consistency through a seldom-used methodology, intraclass correlation coefficients. Participants were 135 public employees, the total staff in a local government department. Jobs were clustered into job families through a work analysis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Also, they did not find evidence that job performance can be expected to be highly skewed. Also, Díaz-Vilela et al (2015) found a normal distribution of administrative ratings of task and contextual performance in a sample of Spanish public servants. Based on these findings, it can be reasonably assumed that supervisory performance ratings are normally distributed and, therefore, that the reliability correction formula and the selection ratio formula can be applied in the present study.…”
Section: Methodsmentioning
confidence: 94%
“…Also, they did not find evidence that job performance can be expected to be highly skewed. Also, Díaz-Vilela et al (2015) found a normal distribution of administrative ratings of task and contextual performance in a sample of Spanish public servants. Based on these findings, it can be reasonably assumed that supervisory performance ratings are normally distributed and, therefore, that the reliability correction formula and the selection ratio formula can be applied in the present study.…”
Section: Methodsmentioning
confidence: 94%
“…Task performance assessment scale : this tool was composed of 14 items based on the task inventory of a previous job analysis [44]. The participants used a computer application to evaluate the quality and frequency with which the main characters in each video performed the tasks associated with their jobs [45].…”
Section: Methodsmentioning
confidence: 99%
“…These performance samples included a series of performance task activities habitually carried out by administrative and office staff, as well as the contextual behaviours of the employee in work interactions. These administrative tasks were identified by analyzing a previous post (Díaz-Vilela et al, 2015). In relation to contextual behaviours, according to an assessment by a group of experts and administrative professionals, the ten most representative and realistic descriptions were selected from the 20 created, in line with Borman and Motowidlo's (1993) that such courses were useless.…”
Section: Materials and Toolsmentioning
confidence: 99%